Atypical Spitz tumour with positive sentinel lymph node. Issue 3 (June 2013) - Lazzeri, Davide; Pieroni, Marzia; De Rosa, Maurizio; Agostini, Tommaso
Abstract A 16-year-old young man presented with an atypical Spitz tumour of the left buttock with involvement of the left inguinal sentinel node. After inguinal lymphadenectomy, none among the further 21 left inguinal lymph nodes excised was positive. The patient has been free of disease for 39 months. Reviewing published reports, 68 of 147 patients with atypical Spitz tumours having sentinel node mapping had positive nodes. Complete nodal dissection was performed in 66 of these 68 patients. All these patients with a positive sentinel node including this patient were alive and disease-free, with a mean follow-up of 35.8 months. Doubts about the exact nature of atypical Spitz tumours still persist. Although it does not seem to behave like conventional melanomas since prognosis is highly favourable despite a high incidence of sentinel node deposits, interpretations of these nodal involvements are still debated. A longer follow-up period of surveillance should be useful to definitively disclose this question. A literature review to provide an analysis of current knowledge regarding diagnosis, management, and treatment options was undertaken. Furthermore, current misconcepts leading to under-treatment as well as over-treatment, new trends in diagnosis, and surgical approach are discussed. The real biologic potential of the disease could not often be evaluated by sentinel lymph node status. Although this procedure may have a role, possibly being therapeutic for those patients who have malignant lesions, it produces morbidity and outcomes that are sometimes difficult to interpret in this type of pigmented lesions. Thus, it should be reserved to selected patients.